The Authoritative Dimension in Social Relations - Bellini, Pier Paolo (Italian Sociological Review, 2018)
The catastrophic consequences of the abuse of authority perpetrated during the first half of the secolo breve have led to globally dimensioned cultural, social and psychological pressures towards the formulation of legal limitations able to prevent repetition of such aberrations. The ‘democratic’ wind, though undeniably effective in encouraging enhanced appreciation of, and undifferentiated respect for, each individual, has nevertheless proved weaker when required to find an appropriate theoretical and practical repositioning of the authoritative dimension proper to any social relationship, whether at systemic, interpersonal or individual level. The purpose of this inquiry is to encourage updated reflections on the role of the authoritative dimension in social and personal development processes.